Evaluating The Model of Realization of The Benefits of The Success of The Strategic Planning Information System at Higher Education in Indonesia - Bernadus, Gunawan Sudarsono; Aedah, Abd Rahman; Aang, Subiyakto (ICIC International, 2021)
Information System Strategic Planning (ISSP) at Higher Education in Indonesia is still very much needed because it can provide the realization of benefits for success. Success can be felt in terms of benefits realization. Currently, there are many studies related to the ISSP; however, there are still not many studies that discuss the evaluation of a successful ISSP model in terms of its benefit realization. The purpose of this study is to evaluate a model for the realization of the benefits of the success of strategic planning in information systems using Partial Least Squares Structural Equation Modeling (PLS-SEM). This evaluation used a purposive sampling method involving 166 respondents from the results of both online and offline survey activities at Higher Education in Indonesia. The application used for data processing from this evaluation activity is SmartPLS 3.1. The results of this study are statistical results that all variables in the model being evaluated provide validity, reliability, and the power of estimation between variables to the model as a whole. These results are expected to contribute both theoretically and practically in planning the success of the ISSP in Higher Education.